Ayurvedic Management of Idiopathic Full-Thickness Macular Hole with Anatomical Closure on OCT: A Case Report - Narayanan, Nelliakkattu; Sreekala , Nelliakattu N P; Parameswaran, Sreekanth N; Parayil, Chintuja J; Soman, Sumesh; Sukumaran, Krishnendu (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Macular hole (MH) is a vitreoretinal disease characterized by a full-thickness neurosensory retinal defect in the center of the macula. Although there is no direct correlation, based on the symptomatic presentation of the patient, full thickness Macular Hole (FTMH) can be correlated to Vataja Kaca. Case Presentation: A 61-year-old male presented with a four-month history of blurred vision in the right eye (RE), especially with difficulty in reading small letters, with central scotoma (blurry spot in the center of the visual field), with no marked distortion of lines. Optical Coherence Tomography (OCT) confirmed the diagnosis of FTMH. Intervention: The patient underwent a structured Ayurvedic treatment protocol, focusing on Ama pachana, Samana (palliative), Snehana (unctuous therapy), Brmhana (nourishing), and Vatahara line of treatment. Outcome: After five months, the patient reported progressive improvement in visual clarity of the RE with the absence of central scotoma. Visual acuity improved to 6/9 (logMAR 0.176) in the RE from baseline 6/24 (logMAR 0.602), while near vision in RE improved to N12 from baseline N24 and OCT shows complete closure of the hole. Conclusion: This case highlights the potential efficacy of Ayurvedic therapies in the management of a FTMH, necessitating further larger-scale trials and research in this field for validation.